The Impact of Aromatherapy Gelatin Cold Compresses on the Concentration Level of Students in the Covid-19 Pandemic Online Class - Elvira Sari Dewi SKep, M.Biomed; Fifi Afifatus Zakiya SKep; Karina Wulan Mei SKep; Gusde Arimbawa SKep; Nurul Evi SKep, MKep, SpKepMat (SAGE Publishing, 2024)
Introduction Stressful circumstances presented by the Covid-19 pandemic led to reduced levels of study concentration among students, and these conditions had been linked with dopamine levels. Objectives This study aimed to evaluate the impact of aromatherapy gelatin cold compress in increasing the study concentration of students by decreasing stress levels and elevating dopamine levels during the Covid-19 pandemic online class. Methods The study participants consisted of 42 students, who were selected using the simple random sampling method. Subsequently, the participants were comparably divided into control and treatment groups. Compress intervention was given to the treatment group on the forehead for 10 min before studying online. The Visual Analog Scale (VAS) and Stroop test were then used to determine stress and concentration levels of the students, respectively. The catecholamine fractionated urine was used to measure dopamine levels. Analysis was carried out using Paired T-test and Independent T-test with α = 0.05 and CI = 95%. Results The mean value of the VAS before and after treatment was 5.81 ± 2.48 and 5.28 ± 2.61 in the control ( p  = 0.205), as well as 6.28 ± 1.62 and 4.38 ± 1.89 in the treatment group ( p  = 0.000). The mean interference score of the Stroop test before and after treatment was 13.16 ± 1.05 and 13.22 ± 1.31 among the controls ( p  = 0.947), while 13.35 ± 6.94 and 8.92 ± 5.91 were recorded in the treatment group ( p  = 0.000). The average dopamine levels before and after the intervention were 145.50 ± 7.94 mg/mL and 146.65 ± 8.23 mg/mL creatinine among the controls ( p  = 0.542), while 145.35 ± 1.03 mg/mL and 265.18 ± 1.27 mg/mL creatinine were obtained in the treatment group ( p  = 0.01). Furthermore, the results showed that the creatinine levels were within the normal ranges. The Independent T-test of stress, concentration, and dopamine levels obtained p  = 0.024, p  = 0.010, and p  = 0.090, respectively. Conclusion Aromatherapy gelatin cold compress was effective in increasing study concentration by decreasing stress levels and increasing dopamine levels during the Covid-19 pandemic online class.